2019
DOI: 10.1080/14786435.2019.1695163
|View full text |Cite
|
Sign up to set email alerts
|

Role of axial twin boundaries on deformation mechanisms in Cu nanopillars

Abstract: In recent years, twinned nanopillars have attracted tremendous attention for research due to their superior mechanical properties. However, most of the studies were focused on nanopillars with twin boundaries (TBs) perpendicular to loading direction. Nanopillars with TBs parallel to loading direction have received minimal interest. In this backdrop, the present study is aimed at understanding the role of axial TBs on strength and deformation behaviour of Cu nanopillars using atomistic simulations. Tensile and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The deformation behaviour of [110] BCC Fe nanowires with twin boundaries oriented parallel to the loading direction were considered in this study (Figure 1). The nanopillar is enclosed by [1][2][3][4][5][6][7][8][9][10][11] and [1-1-2] type side surfaces. The number of TBs is varied from one to three (Figure 1a-c).…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation behaviour of [110] BCC Fe nanowires with twin boundaries oriented parallel to the loading direction were considered in this study (Figure 1). The nanopillar is enclosed by [1][2][3][4][5][6][7][8][9][10][11] and [1-1-2] type side surfaces. The number of TBs is varied from one to three (Figure 1a-c).…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In order to understand the deformation behaviour of twinned FCC nanowires/nanopillars, many experimental and atomistic simulation studies have been carried out in the literature [2,[6][7][8][9]. The results have shown that depending on the orientation of the TBs with respect to the loading direction, deformation mechanisms vary in nanowires and also many novel deformation mechanisms have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the strengthening effect of TBs strongly depends on the TB spacing [9,10,14,15]. Generally, the yield strength of twinned nanopillars increases with decreasing twin boundary (TB) spacing [10,13,14] resembling the Hall-Petch type behaviour in polycrystalline materials. This strengthening effect in twinned nanopillars has been attributed to the additional repulsive force exerted by TBs on dislocation nucleation and glide [16,17,18].…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of TBs has become a well-known means of strengthening method in nanopillars and nanocrystalline materials. As a result, many experimental and atomistic simulation studies have been performed on twinned nanopillars containing high density of TBs [9,10,11,12,13]. These studies have revealed that the introduction of TBs increases the strength along with ductility of twinned nanopillars as compared to their twin free counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation